Optimasi Komposisi Bahan Baku Waste Paper Untuk Menekan Direct Material Cost Menggunakan Metode Taguchi (Studi Kasus di PT. Kertas Karawang) - Simpati Samuel Tasane; Annisa Indah Pratiwi; Rizki Amalia Pratiwi (2477 - 6165, 2025)
This research aims to optimize the composition of waste paper raw materials consisting of SOP, SWL, and OMG in the paper production process at PT. Kertas Karawang. The Taguchi method was employed using an L9 (33) orthogonal array design with three replications for each factor combination. The ANOVA results indicated that SWL had the most dominant contribution of 39.86%, followed by SOP with 19.36%, while OMG was not significant and therefore pooled into the error term of 40.78%. The optimal setting for cost was achieved with the composition of SOP 10%, SWL 10%, and OMG 80%, resulting in production cost of Rp 1,328,123/ton. Meanwhile, the optimal setting for brightness was obtained at SOP 10%, SWL 40%, and OMG 50%, producing a brightness level of 72.46%. However, a compromise setting of SOP 20%, SWL 30–40%, and OMG 20% was considered more balanced, as it reduced the cost to Rp 1,371,755/ton while maintaining brightness at 72.35%. These findings demonstrate that the Taguchi method is effective in determining the optimal raw material composition, enabling the company to reduce production costs without sacrificing product quality.